Idiopathic Hypercalciuria in Children With Vesico Ureteral Reflux and Recurrent Urinary Tract Infection - Mahmoodzadeh, Hashem; Nikibakhsh, Ahmad Ali; Karamyyar, Mohammad; Gheibi, Shahsanam; Gholizadeh, Shima; Hooshmand, Hamid Reza (Urology Journal, 2010)
Purpose: Our aim was to determine association of vesicoureteral reflux (VUR) and idiopathic hypercalciuria in children with recurrent and single episode of urinary tract infection (UTI). Materials and Methods: The study group consisted of 45 children with VUR and recurrent UTI, and 2 control groups: 45 normal healthy children (control group 1) and 45 children with VUR and single episode of UTI (control group 2). Idiopathic hypercalciuria was defined as urine calcium to creatinine ratio more than 0.8 (mg/mg) in infants younger than 1 year old, and more than 0.2 (mg/mg) in older children (without any detectable causes for hypercalciuria). Results: The study group consisted of 26 (57.8%) girls and 19 (42.2%) boys, with the mean age of 41.14 ± 22.1 months. Nine (20%) subjects had hypercalciuria. The control group 1 composed of 22 (48.9%) girls and 23 (51.1%) boys, with the mean age of 43.98 ± 16.23 months. In this group, 6 subjects (13.3%) with hypercalciuria were detected. The control group 2 composed of 23 (51.1%) girls and 22 (48.9%) boys, with the mean age of 39.96 ± 24.2 months. In group 2, 7 subjects (15.6%) with hypercalciuria were detected. Conclusion: Comparison between such results was not statistically significant. Despite reports of different studies about accompanying of hypercalciuria with recurrent UTI with or without anatomical abnormalities, according to the present study, idiopathic hypercalciuria is not a major contributing factor to recurrent UTI in children with VUR.